Use of intravenous magnesium to treat acute onset atrial fibrillation: a meta‐analysis - Ho, Kwok M (BMJ Group, 2007)
OBJECTIVES: To assess the effects of intravenous magnesium on converting acute onset atrial fibrillation to sinus rhythm, reducing ventricular response and risk of bradycardia. DESIGN AND DATA SOURCES: Randomised controlled trials evaluating intravenous magnesium to treat acute onset atrial fibrillation from MEDLINE (1966 to 2006), EMBASE (1990 to 2006) and Cochrane Controlled Trials Register without language restrictions. REVIEW METHODS: Two researchers independently performed the literature search and data extraction. RESULTS: 10 randomised controlled trials, including a total of 515 patients with acute onset atrial fibrillation, were considered. Intravenous magnesium was not effective in converting acute onset atrial fibrillation to sinus rhythm when compared to placebo or an alternative antiarrhythmic drug. When compared to placebo, adding intravenous magnesium to digoxin increased the proportion of patients with a ventricular response <100 beats/min (58.8% vs 32.6%; OR 3.2, 95% CI 1.93 to 5.42; p<0.001). When compared to calcium antagonists or amiodarone, intravenous magnesium was less effective in reducing the ventricular response (21.4% vs 58.5%; OR 0.19, 95% CI 0.09 to 0.44; p<0.001) but also less likely to induce significant bradycardia or atrioventricular block (0% vs 9.2%; OR 0.13, 95% CI 0.02 to 0.76; p = 0.02). The use of intravenous magnesium was associated with transient minor symptoms of flushing, tingling and dizziness in about 17% of the patients (OR 14.5, 95% CI 3.7 to 56.7; p<0.001). CONCLUSIONS: Adding intravenous magnesium to digoxin reduces fast ventricular response in acute onset atrial fibrillation. The effect of intravenous magnesium on the ventricular rate and its cardiovascular side effects are less significant than other calcium antagonists or amiodarone. Intravenous magnesium can be considered as a safe adjunct to digoxin in controlling the ventricular response in atrial fibrillation.